ANALISIS FUNDAMENTAL UNTUK MENENTUKAN NILAI INTRINSIK PT PEGADAIAN - , kusnendar ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Determination of intrinsic value is a basic and crucial part of the process of determining equity price in order to optimize the fresh money from IPO. A brief analysis of macro economics, business environment and strategies, reliability of financial data, and analysis of financial statement are needed in determination of fundamental value. In this thesis, financial statements are analised using Least Square Method and random walk trend analysis method, interchangable depend on the data. Based on these analysis, predicted financial statement and cash flow are taken. The valuation method is Free Cash Flows to Equity (FCFE) method. National macroeconomics supported PT Pegadaianâs businesses to grow up. Also, PT Pegadaian did business in very good strategies, such as product differentiation and proper market orientation. Return market is taken from jakarta composite index (IHSG) at level 11,20%. Cost of Capital determined using CAPM at level 6,855%. FCFEâs growth is assumed 5% yearly. Free risk return taken from the average of Surat Perbendaharaan Negara (SPN) or government bond quarterly rate at 3,79%. Beta was taken fromthe average of the companies of financial industries listed at Bursa Efek Indonesia(BEI) at level 0,4136.Intrinsic value of PT Pegadaian is sum up of the present value of FCFE 2013, FCFE 2014, and present value ofthecontinuing value. The result isRp400.267.704.053.204,00.